A Prospective Evaluation of Opioid Consumption Following Orthopaedic Foot and Ankle Surgery: Utilization Patterns and Prescribing Guidelines. Issue 3 (14th September 2018) - Saini, Sundeep; McDonald, Elizabeth; Nicholson, Kristen; Rogero, Ryan; Chapter, Megan; Winters, Brian; Pedowitz, David; Raikin, Steven; Daniel, Joseph
Category: Other Introduction/Purpose: The purpose of our study was to assess opioid consumption patterns following outpatient orthopaedic foot and ankle procedures in order to develop a pragmatic approach to narcotic drug prescription. Methods: Patients undergoing outpatient orthopaedic foot and ankle procedures who met inclusion criteria had the following prospective information collected: patient demographics, preoperative health history and Visual Analog Scale (VAS), anesthesia type, procedural details, and opioid prescription and consumption details. Utilization rates were compared using the Man-Whitney Test or the Kruskall-Wallis analysis of variance test with post-hoc Dunn's multiple comparison test. Results: A total of 1, 009 of 1, 027 patients were included in this study (mean age: 49 years). Overall, patients consumed a median of 20 pills whereas the median number of pills prescribed was 40. This resulted in a utilization rate of 51% and nearly 21, 196 pills left unused. Patients who received forefoot surgery used 6 pills less than those receiving hindfoot/ankle surgery (p=0.002). Patients between the ages of 60-79 consumed significantly less than those between 18-59 years old (p<0.012). Patients with preoperative VAS score =77 (p=0.002) or self-reported anxiety (p=0.070) a had an increase in opioid consumption compared to those who did not. Conclusion: Our study demonstrates that patients who undergo orthopaedic foot and ankle procedures are overprescribed narcotic medication by nearly twice the amount that is actually consumed. This leads to a significant surplus of narcotics available for potential diversion. We recommend that surgeons judiciously administer opioid prescriptions based on their patients' consumption patterns and anatomic location of surgery.